Sida cordifolia L.: Ethnobotany, Phytochemistry, Phytonanotechnology, and Commercial Application - Kumar, Sachin; Kumar, Sandeep; Vishnoi, Vineet Kumar; Kumar, Pradeep; Maheshwari, Dinesh Kumar (Current Pharmaceutical Biotechnology, 2024)
Background: After a period of prolonged indifference, where synthetic drugs were preferred, interest in the biological aspects and bioactive ingredients of plants accountable for therapeutic potential has been explored eminently. Sida cordifolia L. is a perennial herb that has been widely utilized in Indian (Ayurveda, Unani, and Siddha), American, and Chinese folk medicine and herbalism practice for curing a wide range of ailments in human beings. Objectives: The goal of this review is to elucidate indigenous knowledge parallelly with the pharmacotherapeutics potential of Sida cordifolia L. against various diseases. It is also intended to display pertinent information related to nanoparticle profiling. Methods: In the current comprehensive study, web-based searches were performed by using several databases, such as Google Scholar, PubMed, ResearchGate, Science Direct, and Scopus, to figure out relevant research work and data published in academic journals from 1930 to July, 2023 using single or combination of keywords listed herewith. Results: More than 50 chemical constituents, including quinazoline and phenethylamine alkaloids, flavones, flavonol, phytosterol, fatty acids, etc., were reported to be found in different parts of healthy plants. Apart from traditional claims and pharmacological aspects, several marketed herbal formulations and granted patents were also described. Conclusion: Several in-vitro and in-vivo studies validated the usage of S. cordifolia as antiinflammatory, antibacterial, antifungal, antiprotozoal, anthelmintic, anticancer, antiulcer, cardioprotective, hypoglycemic, etc. agent. Few patents are also related to S. cordifolia , and more research work needs to be carried out for its potential granted to use as an antiviral agent and other new drug discovery molecules.
Keywords: Sida cordifolia L